Autonomy preferences and behaviors towards asthma medication in online asthma education: a secondary analysis of a cluster randomized controlled trial in adults with asthma - Eck, Stefanie; Baumgärtel, Andrea; Hapfelmeier, Alexander; Linde, Klaus; Sanftenberg, Linda; Stark, Stefanie; Schneider, Antonius (European Clinical Respiratory Journal, 2025)
Objective: Education programs are essential to involve individuals with asthma in disease management and improve outcomes. We aimed to investigate the effects of a pilot-tested online asthma education program (eAEP) on autonomy preferences and medication behavior in adults with asthma in general practices. Methods: We performed a pre-planned secondary analysis of a cluster randomized trial comparing the eAEP with usual care (UC) in terms of Asthma Knowledge Test (AKT) scores. The Autonomy Preference Index (API) was used to assess patients’ preferences for information (information preference) and involvement in medical decisions (participation preference). Participants evaluated eight statements regarding medication behavior. Outcomes were analyzed at baseline and six months. Results: A total of 108 asthma patients (mean age: 47 years, 59% female) were analyzed. Increases in AKT scores were substantially larger in intervention groups (7.9 (95% CI 4.9–10.8), p < 0.001). API subscale scores increased in intervention and control groups, but group-differences were not statistically significant (participation preference: 2.8 (95% CI −4.1–9.6), p = 0.421; information preference: 1.1 (95% CI −1.8–4.1), p = 0.471). There was a positive correlation between changes in AKT and participation preference (r = 0.27, p = 0.031), but not information preference scores (r = 0.08, p = 0.472). Regarding medication behavior, there were some improvements in individual items in intervention groups, but no consistent patterns indicating a clear influence of API scores. Conclusions: The eAEP did not result in larger increases in autonomy preferences compared to UC, but indicated beneficial effects on some forms of medication behavior. Larger studies are required for further insights.
CRIS-Team Scopus Importer:2025-12-26
Keywords: adherence; Asthma; autonomy; decision-making; digital intervention; education; primary care